PENGGUNAAN TEKNIK AUDIT BERBASIS KOMPUTER MELALUI TAHAPAN PROSEDUR AUDIT DAN DAMPAKNYA TERHADAP KINERJA AUDITOR - Amilin -; Erawan Susanto (Sekolah Tinggi Ilmu Ekonomi Gentiaras, 2014)
The purpose of research is to investigate the influence of Computer Assisted AuditTechniques (CAATs) to auditor performance with audit procedure as intervening variable. There are60 respondents of independent auditors who working at CPA firm in Jakarta. The sampling methodto select research sample is convenience sampling method.Hyphotesis testing use a path analysis method. The result of this research shows thatCAATs can be direct influence to auditor performance and audit procedure not as interveningvariable.